Increasing Student Literacy Abilities Supporting The Internship Program At The Faculty Of Economics, Muhammadiyah University, Semarang - Yustinah Yustinah; Faqih Sulthan (International Journal Labs, 2024)
This research improved the students' literacy skills based on management and accounting in supporting the internship program at the economic faculty of Universitas Muhammadiyah Semarang. The researchers improved literacy skills by preparing, promoting, and evaluating the treatment. The content of management and accountancy covered the managerial system, such as (1) planning, (2) implementing, (3) evaluating, and (4) empowering, starting from the plan, control, evaluation, and decision-making. The subjects consisted of the fifth semesters of the management study program and accountancy study program who joined the Indonesian language course. This descriptive statistic research collected the data from Google Forms. The results showed that planning obtained a percentage of 59.9%, implementation with 57.25%, and evaluation with 62.3%. The results indicated the students’ literacy skills needed improvements.